Análisis de las políticas de crédito aplicada por la Cooperativa de Ahorro y Crédito Juan Pio de Mora en la ciudad de Guaranda y su incidencia en sus resultados financieros en el año 2020 - Patiño Aragón, Juan Gabriel (2022)
The present analysis of the research project, focuses the study on the factors that affect the delinquency of the overdue portfolio in the Juan Pio de Mora savings and credit cooperative, which allows to recognize the factors by which the increase of the overdue portfolio is seen in cut to the month of January, also provides greater knowledge about the internal management of the credits that are overdue, since this also helps to improve the delinquent portfolio maintained by the financial institution, this has been done through the comparative study with cooperatives of segment 2 that is located in the Bolivar area, and thus be able to analyze the state of the portfolio maintained by the Juan Pio de Mora Savings and Credit Cooperative Ltda. in relation to the other financial institutions, the methodology applied was quantitative and based on the results obtained in the surveys and interviews, carried out with the Partners and Heads of Credit allows us to present proposals to the cooperative, so that they analyze the feasibility of restructuring on internal credit policies and thus be able to obtain a reduced rate of delinquency and aging within their credit portfolios